Analýza nákladů vybrané společnosti pomocí metody Activity Based Costing - Jursa, Jan (Vysoké učení technické v Brně. Fakulta podnikatelská, 2020)
Diplomová práce je zaměřena na analýzu nákladů společnosti pomocí metody Activity- Based Costing. V teoretické části práce jsou vymezeny základní poznatky a východiska, které později poslouží pro zpracování druhé části. V praktické části je představen zkoumaný podnik, a zhodnocena jeho hospodářská situace. Dále jsou v podniku analyzovány náklady a důležitý úsek práce je také věnován projektu využití metody Activity-Based Costing. V závěru jsou výsledky této metody zhodnoceny.

Master’s thesis deals with analysis of costs of the selected company. Theoretical part brings on fundamental that is later elaborated in the second part. The selected company is introduced and also the current economic situation is evaluated in the practical part. Later the costs are analyzed and important part of the thesis is dedicated to the project of utilization of the Activity-Based Costing method. Conclusion of the thesis evaluates the results of this method.
Cost Analysis of the Company by Using the Method of Activity Based Costing
Keywords: Activity-Based Costing; náklady; aktivity; nákladové objekty; nepřímé náklady; režie; kalkulace; Activity-Based Costing; costs; activities; cost subjects; indirect costs; overheads; costing